Codeine-induced acute generalized exanthematous pustulosis without IL36RN mutations. (19th June 2018) - Chadli, Zohra; Ladhari, Chayma; Kerkeni, Emna; Djobbi, Amira; Fredj, Nadia B; Chaabane, Amel; Boughattas, Naceur A; Aouam, Karim
Recent studies have suggested an association between mutations in the IL-36RN gene and the onset of pustular generalized. In the literature, only one case of acute generalized exanthematous pustulosis (AGEP) induced by codeine in a patient with IL36RN mutation has been reported. Herein, we reported an unusual case of AGEP caused by codeine in a patient with a history of psoriasis and confirmed by an oral provocation test. In this case, we have shown that the IL36RN gene mutation is not a constant condition in drug-induced AGEP. Clinicians should be aware of this side effect of codeine especially, in patients with a history of psoriasis. More studies are needed to clarify the association between drug-induced AGEP and IL36RN gene mutations.